2021
DOI: 10.1007/s11199-021-01261-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Work and Home Spheres for Teachers, and Longitudinal Associations with Depressive Symptoms in a Swedish Cohort

Abstract: The high level of stress among teachers is a frequently reported problem globally but less is known about how demands and resources among teachers affect depressive symptoms, and to what extent gender differences in these conditions can explain potential differences in depressive symptoms. The present study investigated gender differences in teachers’ self-reported depressive symptoms, and differences in their demands and resources in both work and home spheres. Associations between demands and resources, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…One of the research questions was aimed at identifying the personal sociodemographic factors that were associated with depression symptoms. Personal sociodemographic factors such as gender and marital status were significantly associated with depression, and female teachers and those who were single presented heightened depression symptoms, which was previously reported in other studies [8,48,52,53]. Female teachers are more likely to be emotionally responsive and take on caregiving roles with their leaners as compared to male teachers [54], which not only leads to increased responsibilities outside the scope of their work but greatly contributes to teacher role ambiguity and leads to elevated stress levels, making them more susceptible to depression.…”
Section: Discussionsupporting
confidence: 77%
“…One of the research questions was aimed at identifying the personal sociodemographic factors that were associated with depression symptoms. Personal sociodemographic factors such as gender and marital status were significantly associated with depression, and female teachers and those who were single presented heightened depression symptoms, which was previously reported in other studies [8,48,52,53]. Female teachers are more likely to be emotionally responsive and take on caregiving roles with their leaners as compared to male teachers [54], which not only leads to increased responsibilities outside the scope of their work but greatly contributes to teacher role ambiguity and leads to elevated stress levels, making them more susceptible to depression.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, it is possible that deviations from these expectations are more likely to stand out as counternormative, and therefore, to be perceived as uncivil and/or to generate stronger negative reactions from partners. Gendered expectations might also result in women taking on a larger share of informal caregiving and household responsibilities (Ellemers, 2018; Navaie-Waliser et al, 2002) and in shouldering a disproportionate amount of “emotion work” (e.g., providing emotional support to coworkers) on the job (Hurst et al, 2017; Stengård et al, 2022). Given that these activities are mentally and emotionally taxing (Cameron et al, 2019; Ellemers, 2018), engaging in them could impact cognitive depletion and negative affect.…”
Section: Methodsmentioning
confidence: 99%
“…In a study of faculty at a research-intensive university, Misra et al (2012) found that female faculty and mothers in particular carried higher loads of housework and care time but worked for no fewer hours than their male counterparts. Stengård et al (2022) used a decade of data on a Swedish cohort of teachers to examine gender differences in time use and depressive symptoms. They found more depressive symptoms, emotional work demands, and unpaid work among female teachers, whereas male teachers spent more time on leisure activities.…”
Section: Contextmentioning
confidence: 99%